FIRST RECORD OF BELONOCHILUS NUMENIUS (SAY, 1832) (HEMIPTERA: HETEROPTERA: LYGAEIDAE) FROM MONTENEGRO (Acta Entomologica Serbica, 2020)
The paper presents data on the first registration of the bug Belonochilus numenius (Say, 1832) in Montenegro. It was found in the coastal town of Igalo, in an urban area where plane trees grow as ornamental plants, on the fruits of which this species feeds and lives.